Representative Residential LV Feeders: A Case Study for the North West of England - Rigoni, Valentin; Ochoa, Luis F.; Chicco, Gianfranco; Navarro-Espinosa, Alejandro; Gözel, Tuba (IEEE, 2016)
[No abstract available]
IEEE-Power-and-Energy-Society General Meeting (PESGM) -- JUL 17-21, 2016 -- Boston, MA